Analisis Kesulitan Belajar Membaca pada Pembelajaran Bahasa Indonesia di Kelas 5 SD 5 Karangbener - Nadine ‘Aziizah; Elfa Mahfudhoni; Lovika Ardana Riswari (STIKes Ibnu Sina Ajibarang, 2024)
The inability to learn to read is a problem that results in a student being unable to follow the learning process properly and unable to achieve the expected learning goals. The four basic skills that students must have when studying in elementary schools in Indonesia are listening, speaking, reading and writing. The purpose of writing this paper is to determine and analyze the difficulties of learning to read students in learning Indonesian in class V SD 5 Kaarangbener. This article is the result of an analysis of literature related to the topic of discussion. The model used is a literature survey or literature review. The results of this research show that most students still do not understand when the teacher provides Indonesian language material. There are several factors that cause students to have difficulty learning Indonesian. Based on these results, it can be concluded that class V students at SD 5 Karangbener still have difficulty reading when learning Indonesian.